2019
DOI: 10.1021/acs.inorgchem.8b03225
|View full text |Cite
|
Sign up to set email alerts
|

Isostructural Tb3+/Eu3+ Co-Doped Metal–Organic Framework Based on Pyridine-Containing Dicarboxylate Ligands for Ratiometric Luminescence Temperature Sensing

Abstract: In this work, we prepared two types of isostructural Ln 3+ -based metal−organic frameworks (LnMOFs) under solvothermal conditions, where two structurally similar pyridine-containing dicarboxylate ligands, 6-(4-carboxyphenyl)nicotinic acid and [2,2′-bipyridine]-5,5′-dicarboxylic acid, were used as the organic linkers. The as-synthesized LnMOF compounds were characterized using single-crystal X-ray diffraction (XRD), powder XRD, and thermogravimetric analysis. With the lanthanide co-doping approach, two mixed Ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(65 citation statements)
references
References 43 publications
3
62
0
Order By: Relevance
“…However, these mentioned sensors have some limitations, for their large size, use of electrical modules, invasiveness and so on. To overcome these weaknesses, luminescence‐based materials, including up‐conversion RE‐oxide materials and lanthanide metal‐organic frameworks (LnMOFs), have been explored to use as temperature sensing for their unique advantages of contactless measurement and large‐scale imaging , …”
Section: Resultsmentioning
confidence: 99%
“…However, these mentioned sensors have some limitations, for their large size, use of electrical modules, invasiveness and so on. To overcome these weaknesses, luminescence‐based materials, including up‐conversion RE‐oxide materials and lanthanide metal‐organic frameworks (LnMOFs), have been explored to use as temperature sensing for their unique advantages of contactless measurement and large‐scale imaging , …”
Section: Resultsmentioning
confidence: 99%
“…For example, Qian's report proposes Tb‐based MOF for luminescence detection of uric acid. And Eu‐based MOF sensing research for explosive picric acid . In addition, the d 10 center coordination polymer has been studied because it exhibits excellent luminescence ability in combination with functional ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al demonstrated that different numbers of pyridine units in the ligand resulted in a ligand with different T 1 state energy values and changed the sensitization efficiency of Ln 3+ . [ 50 ] Specifically, the QY of Tb‐bpydc, with its two pyridine units, exhibits twofold higher activity than Tb‐cpna, which had only one pyridine unit. The result indicates that modifying the pyridine unit in the ligand enhances the ligand's sensitization for Tb 3+ , as evidenced by the improved Tb 3+ ‐to‐Eu 3+ EnT efficiency.…”
Section: Engineering Ent Processes In Mofsmentioning
confidence: 99%